The Renaissance of Conspiracy Theories about Brainwashing - Aleknonis, Gintaras (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] The discourse of information warfare, challenges posed by adverse propaganda and political declarations about the need to protect the society from misleading information all create favorable conditions for new research on brainwashing. This article examines the new wave of studies on brainwashing, which emerged at the turn of the 21st century. An analysis of the historical context of brainwashing encourages the investigation of competitive concepts and reminds us of the negative scientific attitude toward brainwashing from the moment of its inception. The concept of brainwashing is examined as a mature conspiracy theory, which functions on three levels: the primary (or spontaneous), elite initiated (or official) and secondary (or mirror) levels. The principle aim of this article is to reveal the reasons behind the communicative vitality of brainwashing and to disclose the risks posed to democracy, which are created with the misuse of conspiracy theories and similar concepts.